Sodium nitroprusside increases human skeletal muscle blood flow, but does not change flow distribution or glucose uptake - Pitkänen, Olli-Pekka (Blackwell Science Inc, 1999)
1. The role of blood flow as a determinant of skeletal muscle glucose uptake is at present controversial and results of previous studies are confounded by possible direct effects of vasoactive agents on glucose uptake. Since increase in muscle blood flow can be due to increased flow velocity or recruitment of new capillaries, or both, it would be ideal to determine whether the vasoactive agent affects flow distribution or only increases the mean flow. 2. In the present study blood flow, flow distribution and glucose uptake were measured simultaneously in both legs of 10 healthy men (aged 29 ± 1 years, body mass index 24 ± 1 kg m(−2)) using positron emission tomography (PET) combined with [(15)O]H(2)O and [(18)F]fluoro-2-deoxy-D-glucose (FDG). The role of blood flow in muscle glucose uptake was studied by increasing blood flow in one leg with sodium nitroprusside (SNP) and measuring glucose uptake simultaneously in both legs during euglycaemic hyperinsulinaemia (insulin infusion 6 pmol kg(−1) min(−1)). 3. SNP infusion increased skeletal muscle blood flow by 86 % (P < 0·01), but skeletal muscle flow distribution and insulin-stimulated glucose uptake (61·4 ± 7·5 vs. 67·0 ± 7·5 μmol kg(−1) min(−1), control vs. SNP infused leg, not significant), as well as flow distribution between different tissues of the femoral region, remained unchanged. The effect of SNP infusion on blood flow and distribution were unchanged during infusion of physiological levels of insulin (duration, 150 min). 4. Despite a significant increase in mean blood flow induced by an intra-arterial infusion of SNP, glucose uptake and flow distribution remained unchanged in resting muscles of healthy subjects. These findings suggest that SNP, an endothelium-independent vasodilator, increases non-nutritive, but not nutritive flow or capillary recruitment.